A Highly Sensitive Luminescent Dye@MOF Composite for Probing Different Volatile Organic Compounds. Issue 8 (24th March 2016) - Zheng, Jun‐Ping; Ou, Sha; Zhao, Min; Wu, Chuan‐De
Abstract: The probing of volatile organic compounds (VOCs) is critical and challenging in biotechnology and environmental monitoring. Incorporation of luminescent moieties into metal–organic frameworks (MOFs) has produced many unique luminescent sensors for probing different VOCs. The emissions of most MOF sensors are based mainly on the single transitions of luminescent moieties, so the luminescence readouts are only predominant for some special VOCs. We use a natural amino acid derivative as the luminescent moiety to result in a lamellar coordination polymer, and further embed luminescent dye molecules in the crystal matrix to result in a luminescent dye@MOF sensor. The composite sensor exhibits excellent sensitivity for decoding different VOCs with clearly differentiable fluorescence emission by tuning the energy transfer efficiency from the organic ligand to the dye moieties. The composite luminescent sensor is self‐calibrated, and much more stable and instantaneous than other more widely explored luminescent sensors. Abstract : Metal–organic framework sensor : We report an interesting layered coordination network based on the derivative of the natural amino acidl ‐phenylalanine and zinc ions, which can embed Rhodamine B dye to result in a luminescent sensor of Rho@MOF composite, which can detect different volatile organic compounds with clearly differentiable and unique luminescence readouts by tuning the ligand‐to‐dye energy transfer (see figure).